Step * 1 of Lemma first-m-not-reg-property


1. [X] Type
2. metric(X)
3. : ℕ
4. : ℕk ⟶ X
5. (↑m-not-reg(d;s;first-m-not-reg(d;s;k) 1)) ∧ (∀j:ℕk. ¬↑m-not-reg(d;s;j) supposing j < first-m-not-reg(d;s;k) 1) 
   supposing 0 < first-m-not-reg(d;s;k)
6. ∃i:ℕk. (↑m-not-reg(d;s;i)) ⇐⇒ 0 < first-m-not-reg(d;s;k)
⊢ first-m-not-reg(d;s;k) 0 ∈ ℤ ⇐⇒ ∀n:ℕk. m-not-reg(d;s;n) ff
BY
Auto }

1
1. Type
2. metric(X)
3. : ℕ
4. : ℕk ⟶ X
5. (↑m-not-reg(d;s;first-m-not-reg(d;s;k) 1)) ∧ (∀j:ℕk. ¬↑m-not-reg(d;s;j) supposing j < first-m-not-reg(d;s;k) 1) 
   supposing 0 < first-m-not-reg(d;s;k)
6. (∃i:ℕk. (↑m-not-reg(d;s;i)))  0 < first-m-not-reg(d;s;k)
7. (∃i:ℕk. (↑m-not-reg(d;s;i)))  0 < first-m-not-reg(d;s;k)
8. first-m-not-reg(d;s;k) 0 ∈ ℤ
9. : ℕk
⊢ m-not-reg(d;s;n) ff

2
1. Type
2. metric(X)
3. : ℕ
4. : ℕk ⟶ X
5. (↑m-not-reg(d;s;first-m-not-reg(d;s;k) 1)) ∧ (∀j:ℕk. ¬↑m-not-reg(d;s;j) supposing j < first-m-not-reg(d;s;k) 1) 
   supposing 0 < first-m-not-reg(d;s;k)
6. (∃i:ℕk. (↑m-not-reg(d;s;i)))  0 < first-m-not-reg(d;s;k)
7. (∃i:ℕk. (↑m-not-reg(d;s;i)))  0 < first-m-not-reg(d;s;k)
8. ∀n:ℕk. m-not-reg(d;s;n) ff
⊢ first-m-not-reg(d;s;k) 0 ∈ ℤ


Latex:


Latex:

1.  [X]  :  Type
2.  d  :  metric(X)
3.  k  :  \mBbbN{}
4.  s  :  \mBbbN{}k  {}\mrightarrow{}  X
5.  (\muparrow{}m-not-reg(d;s;first-m-not-reg(d;s;k)  -  1))
      \mwedge{}  (\mforall{}j:\mBbbN{}k.  \mneg{}\muparrow{}m-not-reg(d;s;j)  supposing  j  <  first-m-not-reg(d;s;k)  -  1) 
      supposing  0  <  first-m-not-reg(d;s;k)
6.  \mexists{}i:\mBbbN{}k.  (\muparrow{}m-not-reg(d;s;i))  \mLeftarrow{}{}\mRightarrow{}  0  <  first-m-not-reg(d;s;k)
\mvdash{}  first-m-not-reg(d;s;k)  =  0  \mLeftarrow{}{}\mRightarrow{}  \mforall{}n:\mBbbN{}k.  m-not-reg(d;s;n)  =  ff


By


Latex:
Auto




Home Index